Description of The Level of Knowledge and Compliance With Medication Adherence in Hypertension Patients at Waru Health Center - Aprilia, Friski; Maziyah, Alfi (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2024)
Hypertension is an increase in blood pressure >140/90 mmHg. This study aims to evaluate the level of knowledge about hypertension and compliance with taking medication among hypertension sufferers at the Waru Community Health Center. This research uses a quantitative approach with survey methods. The research sample was 99 respondents who visited the Waru Health Center. The information collection instrument was a structured questionnaire which included questions about hypertension knowledge and medication adherence using descriptive methods. The research results show that the level of knowledge about hypertension at the Waru Community Health Center is quite good, with only a small percentage of respondents having adequate knowledge. The results showed that the majority level of knowledge about hypertension was sufficient knowledge, namely 60 respondents (60.6%). The results of the study showed that compliance with taking medication at the Waru Community Health Center was classified as Fairly Compliant. The results showed that the majority of people with hypertension were quite compliant with taking medication, namely 54 respondents (54.5%). These findings indicate the need to increase outreach and education efforts about hypertension in the region. Good knowledge and good medication adherence can contribute to more effective hypertension prevention efforts in the future.